The Effect of Stability Variation on the Antifungal Activities of Selected Chemical Agents - Otegwu T. C.; Durowaiye M. T; Adamu H. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Aspergillus niger has been found to be one of the most prevalent pathogen in yam tuber (genus Dioscorea). The stability of active chemical agents were evaluated under the following environmental factors: temperature, pH and storage. The test combine antifungal agents: Benomyl/Sodium Benzoate (0.2/550μg/ml), Benomyl/Terbinafine hydrochloride (0.05/0.06μg/ml), Benomyl/Trichloroacetic acid (0.2/1.5μg/ml), Benomyl/Trifluoroacetic acid (0.01/8.5μg/ml) were investigated using the agar-well diffusion and agar dilution method against Aspergillus niger spores. The combined antifungal agents exhibited different degree of antifungal activities at 40 ºC, 70 ºC and 100 ºC, while at alkaline pH 9 the antifungal activities of the chemical agents were observed to display low zones of inhibition. There was no significant change at 90% confident limit in the antifungal activities of the four formulated fungicide combinations observed within the four weeks period of evaluation at both room temperature (25-27±2.0 ºC) and refrigerator (4°C and 7°C). The importance of the data from this study, enable recommended storage conditions, retest interval and shelf lives to be established under the influence of a variety of environmental factors, i.e. temperature, duration of storage and pH.